ANALISIS WACANA KRITIS SIFAT KONSUMERISME DI BULAN RAMADAN PADA IKLAN MARJAN BUDOIN 2025 “CALON ARANG” - Fitra Rahmayufa Muhammad; Ageng Soeharno (Universitas Muhammadiyah Jember, 2026)
The phenomenon of the commodification of religious and cultural values in Ramadan advertisements, particularly in the Marjan Budoin 2025 advertisement